HUBUNGAN POWER OTOT TUNGKAI DAN KOORDINASI MATA TANGAN DENGAN KETEPATAN SMASH BOLA VOLI DI CLUB RVC RIMBO PANJANG KABUPATEN KAMPAR - Juliadi, Muhammad; Slamet, Slamet; Sulastio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrak: This study aims to determine whether there is a relationship between leg muscle power and eye and hands coordination with volleyball smash accuracy of rvc volleyball team in Rimbo Panjang of Kampar Regency. This research is correlation research, the population in this study is rvc volleyball team in Rimbo Panjang of Kampar regency. The sample in this study amounted to 12 people. The sample technique used is total sampling, where all populations are sampled. After that, the data is processed statistically, to test normality with the lilifors test and correlation at a significant level (0.05). The first analysis was between leg muscle power (X1) and volleyball smash accuracy of rvc vollyball club in Rimbo Panjang of Kampar Regency (Y), where rtab at a significant level (0.05) = 0.602 means rcount (0.93)> rtab (rtab 0.602), it is means that the hypothesis is accepted and there is a strong relationship between leg muscle power and the results of the smash. The second analysis from X2 and Y, with a smash result where rtab at a significant level (0.05) = 0.602 means rcount (18.30)> rtab (0.602). it means that the hypothesis is accepted and there is a strong relationship between eye and hands coordination with the results of the smash of rvc volleyball team in Rimbo Panjang of Kampar Regency. The third analysis of the relationship of leg muscle power (X1) eye and hands coordination (X2) with the results of smash (Y) obtained, where rtab at a significant level (0.05) = 0.602, means rcount (40.07)> rtab (0.602). So it can be concluded that the relationship between (X1) and (X2) with (Y) or the relationship between leg muscle power and eye and hands coordination with smash accuracy is significant.Kata Kunci : Power, Coordination And Smash